Implementasi Nilai Pancasila Kurikulum Merdeka sebagai Penguatan Jati Diri Anak Usia 5-6 Tahun - utami-kumala-dewi,; Maemonah, (Inspiratif Pendidikan, 2024)
ABSTRACT: Pancasila as one aspect of the development of an independent curriculum really needs to be instilled from an early age, where children aged 5-6 years have a high sense of curiosity. So it is necessary to form habits to strengthen the identity of students who have national values, which can be implemented through the practice of Pancasila values. So, researchers are interested in conducting research at the Pangudi Luhur Jenarwetan Kindergarten, especially aged 5-6 years, to find out what habits the institution has implemented, to strengthen identity through the Pancasila values ​​of the Independent Curriculum. The researcher used a qualitative research method with a phenomenological approach, while the research subjects were Pangudi Luhur Jenarwetan Kindergarten students in group B with a total of 12 students and 1 class teacher and school principal. The results of this research are similar to the habituation of the Pangudi Luhur Jenarwetan Kindergarten institution, which is the habituation carried out by this institution to train students' identity. One of the instilling habits based on Pancasila indicators includes: first principle (reading prayers according to students' beliefs, worship practices, introduction to various religions and places of worship); second principle (respect and respect educators by shaking hands, giving alms, donating mosque renovations, watering herbal plants); third principle (cooperation in placing flags, flag ceremonies, queuing culture); fourth principle (dare to express opinions and present the results of work, clean up the equipment that has been used); fifth principle (sharing food sustenance, playing together, and community service). The application of Pancasila values ​​should not only be implemented by school institutions. However, parental cooperation at home is very necessary to optimize the strengthening of students' identity in the future. Keywords: Implementation of Pancasila Values ​​in The Independent Curriculum, Strengthening Identity, Children Age 5-6 Years